FINANCIAL ANALYSIS OF CRANE GROUP AUSTRALIA - Verdi Arli (Journal of Economics, Business, and Accountancy Ventura, 2010)
Crane group has continued to develop and enhance its manufacturing capabilities. Starting in the mid 1990s, the company has some success as it revamped its network distribution op- erations. This study identifies whether this company has a strong financial fundamentals and whether investment in the company will be of a long term nature. Its financial statements had been analysed during 5 year period (2004 – 2008). The data were compiled from Annual reports; ASX historical information; Government reports; Media Items and Website Data. The analysis will cover company’s recent financial position, performance and cash flow, including liquidity; profitability; short-term asset management; risk; leverage and capital structure; and trend and horizontal analysis over the last five years. It shows that the past financial position, performance and cash flow have no guarantee for future performance. In addition, this report considers that this company has the fundamental criteria required for long term investment. It is recommended that the client monitor the position in 6-12 months in light of the share price at that time, the capital markets and ongoing evidence of Crane Group Limiter’s sales growth in the weakening economy. It cannot be stated that the com- pany is immune to an economic downturn. Crane Group has delivered dividends consistently over the last few years.